Analizar el rendimiento de los receptores en una red TDM/WDM pon (red óptica pasiva) - Romero Chafla, Luis Fernando (2016)
The rapid increase of Internet users deserve transmission rates higher data rates and greater capacity in terms of number of users. However, this should be achieved at a reasonable cost. TDM (Time Division Multiplexing) and WDM (Wavelength Division Multiplexing) technologies are most used. TDM allows us to offer extend services to many users (sacrificing bandwidth), low speed, at a reasonable cost. WDM meanwhile has the capacity to serve a greater number of users and provide higher transmission speeds, but at high cost. The combination of both types of multiplexing gives rise to hybrid WDM / TDM, where you can reach a greater number of users, it is also a good choice until a future high costs of WDM-PON are reduced. This research allows us to analyze the characteristics of the TDM / WDM PON, receivers and then simulate the network by Optisystem software, obtaining values Error Rate Bit or BER (Bit Error Rate) and the quality factor Q (Q -factor), which allow you to compare the performance of the network for different types of photo receptors at different speeds. The study concludes that the data transmission in TDM / WDM PON receiver using the APD (Avalanche Photodiode) gives better performance.